Sawlog quality and tree dimensions of Scots pine 34 years after artificial moose browsing damage - Matala, Juho; Kilpeläinen, Harri; Heräjärvi, Henrik; Wall, Tapio; Verkasalo, Erkki (Silva Fennica)
Moose (Alces alces L.) browsing causes severe damage in Scots pine (Pinus sylvestris L.) seedling stands. The effects of this damage on the quality of sawlogs were studied in a long-term controlled experiment. This article reports the stem size and external quality characteristics of Scots pine stems 34 years after artificial moose browsing damage. Damaging the trees by clipping the main stem at the seedling stage reduced the diameter, height, and tree volume of the trees at the end of the experiment. The tree growth reduction was dependent on the severity of clipping. The differences between the damaged and the control trees were more obvious in diameter than in height at the time of final felling. Stem form defects and vertical branches were the most typical externally detectable defects caused by clipping. Defects in the butt logs were detected in 71–89% of the damaged trees, depending on the clipping treatment severity. The stronger the clipping treatment, the more likely the stem form was defected and the more commonly were vertical branches and crooks detected in the stems. The results indicate that both tree dimensions and stem quality suffer from moose browsing. The findings of this controlled experiment more likely underestimate than overestimate the damage in comparison to real moose browsing. Further analyses are required to assess the effects of browsing damage on the internal quality of sawlogs and subsequent economic outcomes. 2020